Prinsip Tauhid dalam Implementasi Ekonomi Islam - Khaerul Aqbar; Azwar Iskandar (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, Indonesia, 2021)
This research aims to find out the principles of tawhid and its implementation in the Islamic economic system. This research uses qualitative approaches with library research methods and descriptive analysis. The results show that the nature of tawhid in Islam itself is a unanimous surrender to the will of Allah, both regarding worship and muamalah. From the point of view of tawhid, human was created as His caliph or His representative on earth. Natural resources created must be utilized for the fulfillment of the happiness of all mankind. The implication of this view is the existence of a view of universal brotherhood, which then gives rise to social equality and makes natural resources as “amānah” of God who created the universe. This view will not be substantially implemented if it is not accompanied by socio-economic justice. The enforcement of justice and the elimination of all forms of injustice have been emphasized in the Qur'an as the primary mission of Allah's messenger. Based on this foundation, there should be a balance of all economic factors in economic practice and implementation. People should strive to form a society that pursues key values and seeks the establishment of social justice.